Handelbare Umweltrechte als Steuerungsinstrument für den Straßengüterverkehr in sensiblen Regionen: Fallbeispiel Brennerautobahn - Eßer, Anke; Schmedding, David (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The continuous growth of traffic volume in Europe over the past years and the corresponding economic and ecological impacts are the reasons for a recurring discussion of a more sustainability-oriented transport policy. In this context, the implementation of new transport policy instruments is part of the discussion. Against this background, the article investigates to what extent tradeable permits can be an alternative to the existing mix of transport policy instruments. A system of tradeable permits for heavy goods vehicles in ecologically sensitive areas has been designed and subsequently implemented on a theoretical level for one of the alpine corridors. The impact on traffic volume and the environment have been analysed using ad-hoc models. Conclusions drawn from these models can be used as a basis for a future application of such a system.